Sorption Mechanism and Performance of Peat Soil Humin for Methylene Blue and p-Nitrophenol - Sri Juari Santosa; Eko Sri Kunarti; Nurul Hidayat Aprilita; Beti Wulandari; Dhian Nuri Bawani (Universitas Gadjah Mada, 2019)
The responsible mechanism and performance of peat soil humin for the sorption of methylene blue (MB) and p-nitrophenol (p-NP) have been investigated. Humin was obtained from peat soil of Siantan, West Kalimantan, Indonesia, after removing the content of humic and fulvic acids into a NaOH solution using the recommended procedure of International Humic Substances Society (IHSS). The obtained humin was then purified by rigorous stirring in a mixed solution of HCl 0.1 M and HF 0.3 M. Ash content in humin after the purification abruptly decreased from 36.84 to 1.26 wt.% indicating that minerals and other inorganic impurities were mostly removed. Phenolic –OH and carboxyl (–COOH) functional groups contributing to the acidity of humin were in the level of 3.44 and 2.10 mmol/g, respectively. At optimum medium pH of 6.20 for MB and 7.00 for p-NP, –COO– as the deprotonated product of –COOH was the most responsible active site in sorbing MB and p-NP through electrostatic interaction and hydrogen bonding, respectively. The homogeneity of –COO– as the active site for the sorption of MB and p-NP implied that the surface of humin sorbent was energetically uniform and thereby the sorption of both MB and p-NP followed better the Langmuir than the Freundlich isotherm model with sorption capacity of 0.19 and 0.26 mmol/g and sorption energy of 32.92 and 27.27 kJ/mol, respectively.